Total Productive Maintenance pada Mesin Stemping AIDA 800 Blanking dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) di PT. YXZ - Fadhil Fadhil; Jojo Sumarjo; Oleh Oleh (Jurnal Ilmiah Wahana Pendidikan, 2022)
On the Stamping machine, it is not only the cessation of the machine which results in the cessation of the production process, there are other factors that cause the cessation of production, namely damage to the parts in the die, (Total Productive Maintenance) TPM is a system used to maintain and improve quality. production through maintenance of work equipment and equipment such as Machinery, Equipment and work tools. Overall Equipment Effectiveness (OEE) is a metric that focuses on how effective a production operation is. Results are expressed in a generalized form that allows comparisons between manufacturing units in different industries. From the results of the analysis and calculations carried out in this study using the OEE method, the data obtained that the OEE value of the Stamping machine has a standard value above the average of 98.8%, which means the machine has very good performance. This does not mean that the engine performance is as good as it is now, if it is not carried out properly and regularly, the engine can experience poor performance so that it can disrupt production activities